GÖRSEL SANATLAR EĞİTİMİNDE BİLGİSAYAR TEKNOLOJİSİNDEN YARARLANMA OLANAKLARI - Bora, Mücahit (İdil : sanat ve dil dergisi, 2018)
Basic objective of training with new facilities to make more efficient and effective options produce educational technology; general education, in particular, in order to become a sovereign state of learning information and skills koşulmasıyla work, learning or training can be defined so that the processes of functionality to take effect. In today, educational technology; the realization of the objectives of education for innovative studies, use of new technological system, teaching-learning processes, learning environments, teaching programming and efficient use of human power fields can be aggregated into the five main category. In visual arts training field; used and what of computer technology that should be used are covered; in works two-and three dimensional design, replication, copying, printing to leverage these technologies in processes such as the possibilities of what might happen and what can be exploited in a way that constitutes the foundation of our research. To this aim; in plastic art education that can be used in new computer technologies and what is of computer programs, in what areas and in what ways in which software is being used, additional tools are explored the subject. This research was conducted according to scan-assembly model. Writing resources on the subject were examined, which are being used in the application of computer technologies in person was observed and documented, this technique has been used along with other tools of computer programs has been found in what is going on.